2017
DOI: 10.1039/c7ta01437f
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium–nickel–nickel hydroxide nanoparticles for room temperature catalytic hydrogenation

Abstract: Ru nanoclusters on Ni/Ni(OH)2 nanoparticles supported on carbon (Ru/Ni/Ni(OH)2/C) were successfully prepared and characterized. Ru/Ni/Ni(OH)2/C exhibited an unprecedented catalytic activity for naphthalene hydrogenation at room temperature due to synergetic catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(53 citation statements)
references
References 39 publications
1
52
0
Order By: Relevance
“…The as‐obtained black powder was singed as Ni‐PVP or Ni‐CTAB, respectively. The corresponding Ru‐on‐Ni crystal catalysts were synthesized through galvanic replacement approach . 0.1000 g of the as‐synthesized nickel crystal (Ni‐No, Ni‐PVP or Ni‐CTAB) was dispersed in the pre‐calculated amount of an aqueous solution of RuCl 3 (9.64×10 −3 mol L −1 ), ultrasonic treatment at RT for two hours.…”
Section: Methodsmentioning
confidence: 99%
“…The as‐obtained black powder was singed as Ni‐PVP or Ni‐CTAB, respectively. The corresponding Ru‐on‐Ni crystal catalysts were synthesized through galvanic replacement approach . 0.1000 g of the as‐synthesized nickel crystal (Ni‐No, Ni‐PVP or Ni‐CTAB) was dispersed in the pre‐calculated amount of an aqueous solution of RuCl 3 (9.64×10 −3 mol L −1 ), ultrasonic treatment at RT for two hours.…”
Section: Methodsmentioning
confidence: 99%
“…[39][40][41][42][43] Typically,a n appropriate amount of cobalt(II) chloride hexahydrate (CoCl 2 ·6H 2 O) was dissolved in am ixture of anhydrous ethanol (12.5 mL) and deionized water (82.5 mL), and the mixture was magnetically stirred at RT for 30 min. [39][40][41][42][43] Typically,a n appropriate amount of cobalt(II) chloride hexahydrate (CoCl 2 ·6H 2 O) was dissolved in am ixture of anhydrous ethanol (12.5 mL) and deionized water (82.5 mL), and the mixture was magnetically stirred at RT for 30 min.…”
Section: Catalyst Synthesismentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] For example, Yang et al successfully prepared PtNiCo, PtNi, and PtCo nanoparticles (NPs) by aw et chemical reduction method with oleic acid as ac apping agents and 1,2-hexadecanediol as ar educing agent, [15] and the NPs were supported on as upport (such as carbon). Someb imetallic nanocatalysts have also been utilized, for instance, Pd-Rh, [35] Pt-Ru, [36] Rh-Pt, [37,38] Ru-Ni, [39] and Rh-Ni [40] catalysts. The results confirmed that this catalyst had higherc atalytic activity,h ighers tability,a nd more efficient utilization of the Pt atoms than the Pt/Fe(OH) x catalyst mainly as ar esult of interfacial effects in Pt/FeNi(OH) x .…”
mentioning
confidence: 99%
See 2 more Smart Citations